On the Hypergroups Associated with $n$-ary Relations (Journal of Informatics and Mathematical Sciences, 2014)
The paper deals with hypergroupoids associated with $n$-ary $3n\ge 35$ relations. We give necessary and sufficient condition for an $n$-ary relation such that the hypergroupoid associated with it is a hypergroup or a joinspace. First we analyze for sufficient condition using ternary relation such that the hypergroupoid associated with it is a hypergroup or a joinspace and then we generalize it for an $n$-ary relation.
Keywords: $n$-ary relations; Hypergroups; Joinspces